Mathematical model of methane replacement process in gas hydrate with carbon dioxide in a porous layer - Khasanov M.K.; Stolpovsky M.V.; Kildibaeva S.R. (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования «Южно-Уральский государственный университет (национальный исследовательский университет)», 2017)
In this article we construct a mathematical model and examine the characteristics of the injection of carbon dioxide into the natural layer, rich of the methane and its hydrate in its initial state. We consider the case in which due to the injection of carbon dioxide in the layer two areas are formed: in the first (proximal) region the pores of the layer are saturated with carbon dioxide and its hydrate but in the second (distant) region the pores of the layer are saturated with methane and its hydrate. In the numerical experiments it was established when the pressure increasing on the right border of the layer and decreasing the permeability of the layer or of the pressure of the of carbon dioxide injected, the temperature of the layer can rise at the front of the replacement above the equilibrium temperature of gas hydrate decomposition of methane that corresponds to the appearance of the dissociation border of gas hydrate to methane and water.
Keywords: GAS HYDRATE; POROUS LAYER; METHANE; CARBON DIOXIDE; REPLACEMENT; ГАЗОВЫЙ ГИДРАТ; ПОРИСТЫЙ ПЛАСТ; МЕТАН; ДИОКСИД УГЛЕРОДА; ЗАМЕЩЕНИЕ; 519.6:532.546